(untitled) (Kinesiology, 2020)
It has been well established that plyometric and speed training have positive impacts on fitness parameters in soccer players. The aim of this study was to compare short-term effects of combined plyometric and speed training implemented in the same or separate weekly days on change of direction (COD), maximal sprinting speed (MSS), and repeated sprint ability (RSA) in young soccer players. Twenty-four male players from the same U19 soccer team were distributed into one control group (CG; n = 7, soccer training only) and two experimental groups performing plyometric and speed exercises in the same (CDG; n= 8) or separate weekly days (CWG; n= 9) during a 6-week preparation period. Very likely moderate within-group COD improvements were observed in CDG (ES -0.94 [-1.47 to -0.41]) and CWG (ES -0.97 [-1.52 to -0.42]) groups. Possibly small within-group RSA improvements were also observed in CWG (ES -0.24[-0.64 to 0.16]) and CDG (ES -0.31 [-0.79 to 0.17]) groups. CWG and CDG groups showed possibly small (ES -0.28 [-0.62 to 0.06]) and very likely moderate (ES -0.80 [-1.28 to -0.32]) within-group MSS improvements following the intervention, respectively. A likely moderate (ES 0.71 [0.03 to 1.39]) greater MSS improvement was observed in CDG group than CWG group. It is suggested to supplement normal soccer training with combined plyometric and speed exercises to improve COD, MSS, and RSA performance and implement these exercises in the same weekly session to improve MSS with a greater effect.